Model Penilaian Strategi Pertahanan Matra Laut Negara Kepulauan Berbasis System Dynamic - Martin, Richard; Laksono, Amin Setyo; Riniwati, Harsuko; Widagdo, Setyo (Universitas Trunojoyo Madura, 2022)
The maritime dimension defense strategy model is a part of the Archipelago Marine Defense Strategy, referring to the dynamics or developments in the strategic environment and the capabilities of available national resources. In carrying out an assessment of the defense strategy of the archipelagic nation's sea dimension, it is determined by the influence and interaction of interrelationships between balancing aspects of Naval Forces and Integrated Fleet Weapons Systems (SSAT) with Threat aspects as a complex system, so an analysis is needed to get a value on the assessment defense strategy of the maritime dimension of the archipelagic state, which consists of aspects of developing the strength of the Navy and aspects of Potential Threats. So it needs to be compiled in a dynamic model that can represent a value in the assessment of the marine defense dimension of the archipelagic nation which is projected based on the time dimension up to the next 15 years. In this research, the researchers compiled a system dynamic model approach to obtain an assessment of the value of each variable and sub-variable. The results of the formulation and simulation model on the assessment of the sea dimension defense strategy, obtained values based on the following strategic scenarios: (1) Fleet In Being defense strategy at an index value of 5.72, (2) Blockade defense scenario 5.72, (3) Defense scenario Decesive Battle 5.73, (4) combined scenario between fleet in being and blockade 5.72, (5) combined scenario of fleet in being and decesive battle 5.78, (6) combination scenario of blocakde and decesive battle 5.73 and value sea defense based on current SSAT capabilities in the 15th year of 5.9, included in the alert category/quite safe.